No evidence for host plant associated genetic divergence in a population of Bullacris unicolor (Linnaeus, 1758) (Orthoptera: Pneumoridae) - Sathyan, Rekha; Vanessa C.K. Couldridge, Vanessa Couldridge; Adriaan Engelbrecht, Adriaan Engelbrecht (African Entomology, 2022)
Host-associated genetic differentiation in grasshoppers has received limited attention, due to a lack of information on grasshopper-plant associations. The bladder grasshopper, Bullacris unicolor (Linnaeus, 1758) (Orthoptera: Pneumoridae), is a phytophagous species that can occur on at least six host plants within its geographic range. However, the relationship between host plant association and genetic variation of bladder grasshoppers has not been studied before. In light of this, the present study examined host plant-related genetic [mitochondrial cytochrome oxidase 1 (CO1) and the internal transcribed spacer (ITS) gene regions] and morphological (antennal length, body length, head width, abdomen width, femur length, tibia length and pronotum length) divergence within a population of B. unicolor. We used two plant species, belonging to different families, namely Didelta spinosa (L.fil.) Aiton (Asteraceae) and Roepera morgsana (L.) Beier & Thulin (Zygophyllaceae), to evaluate variation between individuals collected on these two sympatric host plants at a single locality in the Northern Cape, South Africa. The results demonstrated non-significant host related genetic variation with very low values of FST, indicating a low level of variation. The phylogram strongly indicated that there are no host-associated genetic differences in B. unicolor by displaying limited genomic clustering, whereas some differentiation was observed between the morphological measurements of males and females among host plants. Further studies using microsatellite molecular markers may help to discern population genetic structure. In addition, significant host-associated morphological divergence highlights the need to examine the mechanisms by which host utilization affects morphological features.